Effect of melamine-contaminated diet on tissue distribution of melamine and cyanuric acid, blood variables, and egg quality in laying hens - Suchý, P; Novák, P; Zapletal, D; Straková, E (British poultry science, 2014)
1. The aim of the study was to investigate the effect of melamine-contaminated feed (100 mg/kg) on the distribution of melamine and cyanuric acid in the tissues of laying hens. The effect of a 5-week melamine administration in feed on the egg quality and blood variables of layers was also investigated. 2. A total of twenty 36-week-old ISA Brown layers were used in the experiment. The layers were equally divided into an experimental melamine group (n = 10) and a control group without melamine (n = 10). At the end of the experiment, samples of liver, kidney, breast and thigh muscles were collected from all hens and analysed for the presence of melamine and cyanuric acid by gas chromatography and tandem mass spectrometry. 3. Layers receiving the melamine-contaminated diet laid eggs with decreased eggshell strength. The decrease in shell strength was found in weeks 3 and 4 compared to the initial state (week 0) and week 1. 4. Hens receiving the melamine-contaminated diet also exhibited a higher total red blood cell count and lower mean corpuscular haemoglobin compared to the control group. However, melamine at 100 mg/kg feed had no effects on the blood variables of layers. 5. Melamine was detected in all analysed tissues of layers fed on the melamine-contaminated diet, with its mean concentrations decreasing in the following order: kidney (7.43 mg/kg) > breast muscle (3.88 mg/kg) > liver (3.11 mg/kg) > thigh muscle (1.91 mg/kg). The kidney and liver of layers fed on the melamine-contaminated diet also exhibited the presence of cyanuric acid. 6. On the basis of our results, it can be concluded that the biotransformation of melamine into cyanuric acid proceeded mainly in the liver, and cyanuric acid was eliminated in urine.
Keywords: krmivo pro zvířata; kur domácí; Egg Shell; Chickens; počet erytrocytů; plynová chromatografie s hmotnostně spektrometrickou detekcí; vaječná skořápka; Toxicity Tests; triaziny; zvířata; Animal Feed; Biotransformation; Eggs; Gas Chromatography-Mass Spectrometry; biotransformace; testy toxicity; Erythrocyte Count; Triazines; vejce; Liver; Animals; játra